2021
DOI: 10.5194/bg-18-5681-2021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of denitrification and decomposition from three biogeochemical models using laboratory measurements of N<sub>2</sub>, N<sub>2</sub>O and CO<sub>2</sub>

Abstract: Abstract. Biogeochemical models are essential for the prediction and management of nitrogen (N) cycling in agroecosystems, but the accuracy of the denitrification and decomposition sub-modules is critical. Current models were developed before suitable soil N2 flux data were available, which may have led to inaccuracies in how denitrification was described. New measurement techniques, using gas chromatography and isotope-ratio mass spectrometry (IRMS), have enabled the collection of more robust N2, N2O and CO2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…The presented results in Table 1 did not cover the statements and results of the entire study by Grosz et al. (2021).…”
Section: The Denitrification Data Deficitmentioning
confidence: 93%
See 2 more Smart Citations
“…The presented results in Table 1 did not cover the statements and results of the entire study by Grosz et al. (2021).…”
Section: The Denitrification Data Deficitmentioning
confidence: 93%
“…Some models (Del Grosso et al., 2000; Parton et al., 1996) have been partly parameterized with N 2 data that are no longer considered reliable (e.g., based on the acetylene inhibition technique (Weier et al., 1993)) and other model calibrations are simply incomplete. Given the lack of empirical data, approaches to describe soil N 2 are mostly process‐oriented, with the sensitivity of both N 2 and N 2 O to controlling factors constrained based solely on N 2 O data (Grosz et al., 2021; Zhang et al., 2022). In these models, having data from frequent measurements (beyond the common weekly or fortnightly intervals) is crucial.…”
Section: The Denitrification Data Deficitmentioning
confidence: 99%
See 1 more Smart Citation
“…However, single-treatment calibration showed more success to simulate the effects of different soil moisture levels on N 2 O fluxes. In a recent study, Grosz et al (2021) also found it difficult to describe treatments in incubation studies with three N 2 O models (DNDC, CoupModel, and DeNi) that responded to controlling factors in the same direction as measurements with frequencies from only 19 % to 67 %. In CoupModel, soil moisture effects have indirect effects on denitrification through decomposition, nitrification, and gas diffusion processes in which the soil moisture response function and its association with anaerobic conditions were accounted for.…”
Section: Treatment Effectsmentioning
confidence: 99%
“…Having explicit measurements in each layer (i.e., soil-residue mixture and bulk soil layer) of incubated soil cores and having higher measurement frequencies of mineral N and gas emissions within the first 24 h of the experiment are promising tools to improve the reliability of experimental data for modeling. Thirdly, in soil N 2 O modeling, measuring more ancillary variables regarding N cycling (e.g., N 2 , NO) and using state-of-the-art techniques (e.g., 15 N gas flux methods) could help test the validity of model principles (Grosz et al, 2021). Although collecting all data types discussed here is not always possible or practical, we consider that reporting ancillary model outputs regarding N cycle processes even in the absence of observations, particularly the denitrification products, soil oxygen content, and anaerobic fraction, will aid model evaluation efforts, which was not done very often in previous studies.…”
Section: Improving Modeling Practice and Experimental Designmentioning
confidence: 99%